Development And Validation Of Cognitive Diagnostic Assessment (CDA) For Primary Mathematics Learning Of Time - Ling, Carolyn Sia Jia (2017)
This study aims to develop and validate the cognitive diagnostic assessment (CDA) for primary mathematics learning in the topic of “Time”. The CDA is an assessment which can provide meaningful feedback on learner’s cognitive strengths and weaknesses during teaching and learning. In this study, the CDA was developed based on the Assessment Triangle and Attribute Hierarchy Method (AHM). This study involved seven experienced primary mathematics teachers and 1123 primary school pupils. Quantitative data was collected through paper and pencil test while qualitative data was collected via think-aloud interview session. There were two phases included in the development of CDA